Cycles of risk: Associations between menstrual cycle and suicidal ideation among women. (February 2015) - Smith, April; Miller, Saul; Bodell, Lindsay; Ribeiro, Jessica; Joiner, Thomas; Maner, Jon
Highlights: Lower levels of progesterone were associated with greater burdensomeness. Burdensomeness was greater during the follicular phase than the luteal phase. Hormonal variation may underlie determinants of suicidal ideation. Abstract: The current study examined associations between cyclic variation in hormone levels and perceived burdensomeness and thwarted belongingness – two determinants of suicidal ideation. Nineteen participants who experienced suicidal ideation and had normal menstrual cycles were selected out of 1482 college students and completed a series of on-line questionnaires every other day for 1 month. Menstrual cycle status, depressive symptoms, and feelings of perceived burdensomeness and thwarted belongingness were assessed. Hormone levels were estimated based on standardized actuarial data. Lower levels of progesterone were associated with greater feelings of burdensomeness. Perceived burdensomeness was also greater during the follicular phase than the luteal phase. Additionally, lower levels of prolactin were associated with both increased feelings of burdensomeness and thwarted belongingness; however, these associations were not significant after controlling for depression. Results suggest that hormonal variation is associated with the determinants of suicidal ideation and provide further explanation for associations found between the menstrual cycle and suicide risk.